If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x * x + 10 = 0 Multiply x * x 5x2 + 10 = 0 Reorder the terms: 10 + 5x2 = 0 Solving 10 + 5x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x2 = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 5x2 = 0 + -10 5x2 = 0 + -10 Combine like terms: 0 + -10 = -10 5x2 = -10 Divide each side by '5'. x2 = -2 Simplifying x2 = -2 Reorder the terms: 2 + x2 = -2 + 2 Combine like terms: -2 + 2 = 0 2 + x2 = 0 The solution to this equation could not be determined.
| 49.50=16.50 | | 0.95t+0.05(10-t)=0.37(10) | | x-10+x=70 | | 3/7*12 | | 4n-2n=6n | | Ln(-x^2-9)=0 | | x+x+10=70 | | 3x^2+5x-7=5 | | 77=11vanser | | 5x*x-10x=0 | | 6x+3x=4800 | | 6/1m=16 | | 3-4x^2=-97 | | 28/7=36/somethi | | 3x^2+5x-7=y | | r+64.1=-13.2 | | z-10y=90 | | 16=4/5w | | 4d+12=-10d-18+19d | | 3x-20=5x-16 | | N=31 | | -5(x^4-3)+12= | | 8(1/2)(1/2-3(3))= | | -3d+5=9-3d | | Y=2(y+1)+2 | | -3(8x+8)=-5x+33 | | 2-4-(-8)= | | -13t-8=-13t+11 | | 8/9=x-1/6 | | -39+3m=1+3(m+6) | | (a+25)=1 | | x^2+2xy+y^2+2x+2y-1=0 |